An optimized prostate biopsy strategy in patients with a unilateral lesion on prostate magnetic resonance imaging avoids unnecessary biopsies. (July 2022) - Jager, Auke; van Riel, Luigi A.M.J.G.; Postema, Arnoud. W.; de Reijke, Theo M.; van der Sluis, Tim M.; Oddens, Jorg R.
Purpose: The introduction of magnetic resonance imaging (MRI)-targeted biopsy (TBx) besides systematic prostate biopsies has resulted in a discussion on what the optimal prostate biopsy strategy is. The ideal template has high sensitivity for clinically significant prostate cancer (csPCa), while reducing the detection rate of clinically insignificant prostate cancer (iPCa). This study evaluates different biopsy strategies in patients with a unilateral prostate MRI lesion. Methods: Retrospective subgroup analysis of a prospectively managed database consisting of patients undergoing prostate biopsy in two academic centres. Patients with a unilateral lesion (PI-RADS ⩾ 3) on MRI were included for analysis. The primary objective was to evaluate the diagnostic performance for different biopsy approaches compared with bilateral systematic prostate biopsy (SBx) and TBx. Detection rates for csPCa (ISUP ⩾ 2), adjusted csPCa (ISUP ⩾ 3) and iPCa (ISUP = 1) were determined for SBx alone, TBx alone, contralateral SBx combined with TBx and ipsilateral SBx combined with TBx. A subgroup analysis was performed for biopsy-naive patients. Results: A total of 228 patients were included from October 2015 to September 2021. Prostate cancer (PCa) detection rate of combined SBx and TBx was 63.5% for csPCa, 35.5% for adjusted csPCa, and 14% for iPCa. The best performing alternative biopsy strategy was TBx and ipsilateral SBx, which reached a sensitivity of 98.6% (95% CI: 95.1–99.6) for csPCa and 98.8% (95% CI: 96.3–99.9) for adjusted csPCa, missing only 1.4% of csPCa, while reducing iPCa detection by 15.6% compared with SBx and TBx. TBx or SBx alone missed a significant amount of csPCa, with sensitivities of 90.3% (95% CI: 84.4–94.2) and 86.8% (95% CI: 80.4–91.4) for csPCa. Subgroup analysis on biopsy-naive patients showed similar results as the overall group. Conclusion: This study shows that performing TBx with ipsilateral SBx and omitting contralateral SBx is the optimal biopsy strategy in patients with a unilateral MRI lesion. With this strategy, a very limited amount of csPCa is missed and iPCa detection is reduced.